Survey on Concept of Object-Oriented Programming - Mansi Dhirajsinh Parmar; Sarthavi Parmar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
These days, object-oriented programming is regarded as an essential programming concept.The moment Simula brought it into life. The use of object-oriented programming (OOP) has expanded in the software real world due to the future growth of the software business and the advancement of software engineering. The following review examines different oop concepts that are essential to object-orientation, in great detail. Many widely used object-oriented programming languages implement various parts of inheritance and polymorphism. We come to the conclusion that much more work needs to be done to find a middle ground so that these can accomplish OOPs features.